A non-toxigenic Aspergillus flavus strain prevents the spreading of Fusarium verticillioides and fumonisins in maize. (15th July 2020) - Reis, T.A.; Oliveira, T.D.; Zorzete, P.; Faria, P.; Corrêa, B.
Abstract: We evaluated Fusarium verticillioides and fumonisin contamination in maize samples after application of a non-aflatoxigenic Aspergillus flavus strain in the field. The sampling was performed 150 days after planting. The results showed a reduction in F. verticillioides frequency, as well as in fumonisin levels when samples were obtained from field areas treated with non-aflatoxigenic A. flavus strain. These results suggested a competition for substrate or space between fungi reducing the frequency of F. verticillioides and, consequently, fumonisin production. Highlights: Fusarium verticillioides frequency was reduced with an Aspergillus flavus strain. An Aspergillus flavus strain controled fumonisin contamination. Non-toxigenic Aspergillus seem to be an alternative for control fumonisin.